PERBANDINGAN INTENSITAS CAHAYA LAPTOP TERHADAP JARAK PANDANG DAN UKURAN BERBAGAI JENIS LAPTOP - Abdillah, Lutfi; Kadir, Ihsan; Lanto, Muhammad Said (JFT : Jurnal Fisika dan Terapannya, 2014)
This research on Laptop Light Intensity Comparison Against Visibility and Size Different Types of Laptop. The purpose of this study was to compare the laptop light intensity (light source) at various distances users, and compare the laptop light intensity (light source) is produced by several brands of laptops. This research was conducted at the Laboratory of Physics, Faculty of Science and Technology by using luxmeter, stopwatch, meter and protractor. Retrieval of data begins with the selection of laptops ranging from 10 inches, 11.5 inches, and 14 inches then measure the intensity of light emitted from each of the laptops in the interval during the 300 second with a distance of 20 cm-1 m. Make a graph of the results of all the research and explain the graph of the results of the research. Conclusion of the research that has been done is the light intensity obtained at various distances users on laptops 10 inches obtained mixed results, this is because the greater the distance between the sensor luxmeter with a light source (laptop), the smaller the value of the light intensity on the screen luxmeter panel. Greatest light intensity obtained in lapotop 10 inches is the HP laptop (Hewleet Packard) with a value of 5,574 cd, to laptop 11.5 inches Acer laptop that is on the cd value of 6.317, and the 14 inches laptop that is on a Samsung laptop with a value of 8.110 cd.